Real Time Motion Generation for Mobile Robot. Issue 13 (2019) - Gao, Jiuchun; Pashkevich, Anatol; Claveau, Fabien; Chevrel, Philippe
Abstract: The paper proposes a new real time motion generation technique for a mobile robot, which is able to find time-optimal motions along a curved path taking into account capabilities of the driving motors and ensuring the wheels rolling without skidding. The problem is converted to a time-optimal control of a second-order dynamic system under constraints on the control input, the first derivative of output, and mixed constraint on the control variable and the output derivative. After the state space discretization, the original problem is presented as a combinatorial one where the desired robot trajectory corresponds to a shortest path on the relevant graph. To find this path and ensure its real time implementation, a moving window strategy combined with dynamic programming is proposed. Advantages of this approach and its suitability to real time control are illustrated by a case study dealing the fastest motion of the mobile robot along a sinusoidal path.